Design and optimization of remote telecommunication station power system using solar/wind energy - Nor Hanisah, Baharudin (Curtin University of Technology, 2016)
People in remote areas at present are beyond the coverage of conventional telecommunication networks. Telecommunication mobile markets have reached its saturation period and hunted for a new market. The conventional technology of telecommunication mobile networks nowadays is unable to reach the millions of rural user that ready to embrace it. The new technology introduced by WorldGSM is a new solution to reach the threshold of profitable mobile services in rural areas. The telecommunication station introduced is consumed at less than 50W which the whole system can be run alone on solar energy or wind/solar energy on selected site which is Cameron Highlands, Malaysia. The objective of this research is to design and optimize remote telecommunication power system using solar and wind energy.